Target trial emulation of preconception serum vitamin D status on fertility outcomes: a couples-based approach - DiTosto, Julia D.; Caniglia, Ellen C.; Hinkle, Stefanie N.; Sealy, Naria; Schisterman, Enrique F.; Johnstone, Erica; Mendola, Pauline; Mills, James; Hotaling, Jim; Ryan, Ginny; Mumford, Sunni L. (Fertility and sterility, 2025)
To evaluate associations between preconception 25-hydroxyvitamin D (25(OH)D) levels and biomarkers in female and male partners on live birth (LB), pregnancy loss, and semen quality. Secondary analysis using the folic acid and zinc supplementation trial of couples seeking infertility treatment at four US centers (2013–2017). A target trial emulation framework was applied to estimate associations. Couples were observed for 9 months or through pregnancy. Couples seeking infertility treatment. Preconception concentrations of 25(OH)D (primary) and associated biomarkers: vitamin D binding protein, calcium, free vitamin D, bioavailable vitamin D. Live birth and pregnancy loss were ascertained via self-report and medical records. Semen quality was ascertained 6 months after enrollment. Log-binomial regression estimated risk ratios and 95% confidence intervals (CIs). Individual and joint models and effect measure modification by preconception body mass index were considered. Among 2,370 couples, 19.5% of females and 29.9% of males were 25(OH)D deficient. Females with sufficient status had a 28%-higher likelihood of LB than deficient females (95% CI, 1.05–1.56). Female and male 25(OH)D status were associated with LB among those with normal body mass index (sufficient vs. deficient: female adjusted risk ratio [aRR], 1.39; 95% CI, 1.00–1.99; male aRR, 1.51; 95% CI, 1.01–2.25) and among obese female partners (sufficient vs. deficient: aRR, 1.33; 95% CI, 0.95–1.85). Couples whose both partners had higher 25(OH)D status had increased likelihood of LB (both not deficient vs. both deficient aRR, 1.26; 95% CI, 1.00–1.58). No associations were observed with pregnancy loss or semen quality. Similar results were found for all biomarkers except calcium. Preconception vitamin D status and bioavailability impact fertility among couples seeking infertility therapy, likely unrelated to semen quality. Body mass index stratified analyses demonstrated heterogeneous associations. NCT01857310. Emulación de ensayos clínicos sobre el estado de vitamina D en suero preconcepcional y sus efectos sobre los resultados en la fertilidad: un enfoque basado en parejas. Evaluar la asociación entre los niveles preconcepcionales de 25-hidroxivitamina D (25(OH)D) y los biomarcadores en mujeres y sus parejas varones con respecto al nacido vivo (LB), a la pérdida gestacional y a la calidad del semen. Análisis secundario del ensayo de suplementación con ácido fólico y zinc en parejas que buscaban tratamiento de infertilidad en cuatro centros de EE.UU. (2013-2017). Se aplicó un enfoque de emulación de ensayos clínicos para estimar las asociaciones. Las parejas fueron observadas durante 9 meses o hasta el final del embarazo. Clínicas que ofrecen atención en endocrinología reproductiva e infertilidad en los EE.UU. Parejas que buscan tratamiento de infertilidad. Concentración de 25(OH)D antes de la concepción (primarias) y biomarcadores asociados: proteína de unión a la vitamina D, calcio, vitamina D libre, vitamina D biodisponible. Los nacidos vivos y la pérdida del embarazo se recabaron mediante informes de las pacientes y por registros médicos. La calidad del semen se evaluó 6 meses después de la inclusión en el estudio. Se utilizó la regresión log-binomial para estimar las razones de riesgo y los intervalos de confianza (CIs) del 95%. Se consideraron modelos individuales y conjuntos, así como la modificación de medidas de efecto según el índice de masa corporal antes de la concepción. De las 2,370 parejas, el 19.5% de las mujeres y el 29.9% de los hombres presentaron deficiencia de 25(OH)D. Las mujeres con niveles suficientes tuvieron un 28% más de probabilidad de tener un LB en comparación con las mujeres con deficiencia (CI del 95%, 1.05–1.56). El nivel de 25(OH)D en mujeres y hombres se asoció con LB entre aquellos con índice de masa corporal normal (suficiente vs. deficiente: razón de riesgo ajustada [aRR] en mujeres, 1.39; IC del 95%, 1.00–1.99; aRR en hombres, 1.51; IC del 95%, 1.01–2.25) y entre parejas femeninas obesas (suficiente vs. deficiente: aRR, 1.33; IC del 95%, 0.95–1.85). Las parejas en las que ambos miembros tenían niveles altos de 25(OH)D presentaron una mayor probabilidad de LB (ambos sin deficiencia vs. ambos con deficiencia aRR, 1.26; IC del 95%, 1.00–1.58). No se observó asociación con la pérdida gestacional o con la calidad del semen. Se encontraron resultados similares para todos los biomarcadores excepto para el calcio. El estado de vitamina D antes de la concepción y su biodisponibilidad impactan sobre fertilidad en parejas que buscan tratamiento de reproducción, probablemente no relacionado con la calidad del semen. Los análisis estratificados por índice de masa corporal demostraron asociaciones heterogéneas.